High-solar-absorptance CSP coating characterization and reliability testing with isothermal and cyclic loads for service-life prediction. Issue 5 (26th April 2019) - Noč, Luka; Šest, Ervin; Kapun, Gregor; Ruiz-Zepeda, Francisco; Binyamin, Yaniv; Merzel, Franci; Jerman, Ivan
Abstract : Revealed degradation mechanisms in the HSA CSP coatings through accelerated testing and materials characterization enable absorber service life prediction. Abstract : Tower-technology-based concentrated solar power (CSP) promises to deliver electricity prices below 7.3 ¢ per kW h based on thermal energy storage and future renewable-energy harvesting technology. However, the price depends very much on the energy-transformation efficiency. Previous work on absorber coatings showed a reduced absorber efficiency over time. However, due to the extreme thermal and environmental loads during CSP operation, premature failure is expected. The absorber coating's service life, reflected in the energy-transformation efficiency vs. the operating time, is proportional to the profit expected by investors. In this study, using experimental testing combined with advanced analytics and theoretical modelling, we revealed that the field-equivalent thermal loads under isothermal and cyclic conditions facilitates the substrate oxidation. Most importantly, a state-of-the-art industrial coating composed of a black spinel pigment embedded in a silica matrix can serve for more than 10 years with a solar absorptance above 95%. Using advanced material characterization, providing detailed insights into the long-term stability and degradation mechanism under simulated operating conditions, we established the relationship between the coating's performance and its lifetime prediction.